Laboratory changes and levels of biomarkers in localized bacterial infections and sepsis in children - Larysa Pypa; Maryna Murhina (Kazimierz Wielki University, 2017)
Background. The success of sepsis treatment depends on early diagnosis of the generalization of bacterial infection, but the nonspecificity of clinical manifestations often makes the diagnosis delayed. Therefore, the search for highly specific and sensitive biomarkers for early diagnosis of sepsis is relevant. The aim of our research is investigate the laboratory features and diagnostic value of a number of modern biomarkers for the diagnosis of sepsis in children. Materials and methods. of general laboratory studies and determination of CRP level were performed in 115 children with generalized and localized forms of bacterial infections. The main group (47 children) - children with sepsis, a comparison group (68 children) - with a localized bacterial infection of various localization. The age of children was from 1 month. up to 18 years. Grouping was performed according to the presence of signs and symptoms of SIRS and organ dysfunction. Determination of the level of procalcitonin and TNF-α was performed in 31 children of the main group, 45 children in the comparison group and 30 children in the control group (children without signs of inflammation). Prespepsin levels were determined in 16 main group children,14 in the comparison group and26 in the control group. Results. During the study, it was found that the level of leukocytosis was much higher and continued 2.6 times longer in the main group than in the children of the comparison group (p <0.01).Anemia was found in 76.6% of the children in the main group, while in the comparator group, the anemia syndrome was diagnosed 3.7 times less frequently. In the study of CRP in the main group, its level reached 44.7 mg / l and 28.3 mg / l in the comparison group, the specificity and sensitivity for diagnosis of sepsis was 46.8% and 51.5% respectively. The mean TNF-α level in children in the main group was 280.3 pg / ml CI 95% [243.9-316.7], which was 1.5 times higher than in children with a localized bacterial process, where the average level of this cytokine was 186.5 pg / ml CI 95% [163.1-209.9], and 4.2 times higher than that of control group children (65.7 pg / ml CI 95% [56.7-74, 8]). The difference between the groups was statistically significant (p <0.01). Sensitivity and specificity were 61 and 81% (for sepsis diagnosis). In the main group of children, the mean PCT level was 4.06 ng / ml CI 95% [3.34-4.69], and in the comparison group - 0.86 ng / ml CI 95% [0.77-1.03] , in the group of control - 0.024 ng / ml CI 95% [0.02-0.03], between the groups the difference was statistically significant (p <0.01). Sensitivity and specificity were 87% and 90%. The level presepsin in the main group was 1887.5 pg / ml (505.5-3702.5 pg / ml); in the comparator group, 313.5 pg / ml (208-376 pg / ml), in healthy children, the level of presepsin was 109 pg / ml (77.5-160 pg / ml). The difference between the groups is statistically significant (p <0,01). The sensitivity and specificity of determination the level of presepsin in children with sepsis is 92% and 93%, respectively. Conclusions 1. Inchildren with sepsis, leukocytosis is more pronounced in comparison with children with localized bacterial infection, but there is no clear regularity between the severity of the septic state and the magnitude of leukocytosis. 2. Anemia is accompanied by septicemia in almost 76,6% of cases, 3. The most sensitive and specific markers for the development of sepsis are procalcitonin and presepsin and for the diagnosis of bacterial infection, the level of serum presepsin is the most specific and sensitive.